Neisseria cinerea Expresses a Functional Factor H Binding Protein Which Is Recognized by Immune Responses Elicited by Meningococcal Vaccines - Lavender, H; Poncin, K; Tang, C (American Society for Microbiology, 2017)
Neisseria meningitidis is a major cause of bacterial meningitis and sepsis worldwide. Capsular polysaccharide vaccines are available against meningococcal serogroups A, C, W, and Y. More recently two protein-based vaccines, Bexsero and Trumenba, against meningococcal serogroup B strains have been licensed; both vaccines contain meningococcal factor H binding protein (fHbp). fHbp is a surface-exposed lipoprotein that binds the negative complement regulator complement factor H (CFH), thereby inhibiting the alternative pathway of complement activation. Recent analysis of available genomes has indicated that some commensal Neisseria species also contain genes that potentially encode fHbp, although the functions of these genes and how immunization with fHbp-containing vaccines could affect the commensal flora have yet to be established. Here, we show that the commensal species Neisseria cinerea expresses functional fHbp on its surface and that it is responsible for recruitment of CFH by the bacterium. N. cinerea fHbp binds CFH with affinity similar to that of meningococcal fHbp and promotes survival of N. cinerea in human serum. We examined the potential impact of fHbp-containing vaccines on N. cinerea. We found that immunization with Bexsero elicits serum bactericidal activity a gainst N. cinerea, which is primarily directed against fHbp. The shared function of fHbp in N. cinerea and N. meningitidis and cross-reactive responses elicited by Bexsero suggest that the introduction of fHbp-containing vaccines has the potential to affect carriage of N. cinerea and other commensal species.